PENGEMBANGAN SUMBER DAYA MANUSIA SMK NEGERI 1 TAKALAR - Hawirah Hawirah; Andi Jam'an; Amelia Rezky Amin (COMPETITIVENESS, 2021)
Teacher performance plays a role in realizing national education objectives and determining the high quality of education, but teacher performance is influenced by various factors both from within and outside the individual concerned. This research is an effort to get an idea of how teacher performance and influencing factors in order to improve the quality and quality of Vocational High School teachers, especially in SMK Negeri 1 Takalar South Sulawesi. The research was conducted by qualitative method and using primary data obtained through in-depth interviews. The results of research in improving the performance of human resources in SMK Negeri 1 Takalar were carried out by means of time discipline, improving knowledge and skills, procurement and improvement of school infrastructure and establishing good communication. The headmaster's strategy is to improve the performance of human resources by regularly evaluating work programs that have been/have not been achieved by each teacher, knowing and understanding the curriculum that is being run, and teachers are rewarded according to their performance.Keywords: Performance, Teacher Strategy, Human Resources.